Grassroots democracy and development: Learning from the Philippines. (May 2020) - Turok, Ivan; Scheba, Andreas
The Philippines have developed a system of neighbourhood government that other countries could usefully learn from. The barangays give ordinary citizens a voice in decision-making and assist in devolving power from the centre. They also improve the responsiveness of basic public services to local needs. Above all, the institution recognises and legitimises the contribution that communities can make to a robust civil society. The process of participation and engagement helps to harness the agency and resourcefulness of local residents and means that communities are better organised to cope with adversity. Nevertheless, the barangays could be strengthened by advocating physical improvements to their areas and mobilising for additional investment in neighbourhood infrastructure and reconstruction of the built environment.